Association Analysis and Identification of ZmHKT1;5 Variation With Salt-Stress Tolerance - Jiang, Zhilei; Song, Guangshu; Shan, Xiaohui; Wei, Zhengyi; Liu, Yanzhi; Jiang, Chao; Jiang, Yu; Jin, Fengxue; Li, Yidan (Frontiers in Plant Science, 2018)
The high-affinity potassium transporter (HKT) genes are essential for plant salt stress tolerance. However, there were limited studies on HKTs in maize (Zea mays), and it is basically unknown whether natural sequence variations in these genes are associated with the phenotypic variability of salt tolerance. Here, the characterization of ZmHKT1;5 was reported. Under salt stress, ZmHKT1;5 expression increased strongly in salt-tolerant inbred lines, which accompanied a better-balanced Na+/K+ ratio and preferable plant growth. The association between sequence variations in ZmHKT1;5 and salt tolerance was evaluated in a diverse population comprising 54 maize varieties from different maize production regions of China. Two SNPs (A134G and A511G) in the coding region of ZmHKT1;5 were significantly associated with different salt tolerance levels in maize varieties. In addition, the favorable allele of ZmHKT1; 5 identified in salt tolerant maize varieties effectively endowed plant salt tolerance. Transgenic tobacco plants of overexpressing the favorable allele displayed enhanced tolerance to salt stress better than overexpressing the wild type ZmHKT1;5. Our research showed that ZmHKT1;5 expression could effectively enhance salt tolerance by maintaining an optimal Na+/K+ balance and increasing the antioxidant activity that keeps reactive oxygen species (ROS) at a low accumulation level. Especially, the two SNPs in ZmHKT1;5 might be related with new amino acid residues to confer salt tolerance in maize. Key Message: Two SNPs of ZmHKT1;5 related with salt tolerance were identified by association analysis. Overexpressing ZmHKT1;5 in tobaccos showed that the SNPs might enhance its ability to regulating Na+/K+ homeostasis.